Evolution of morphological adaptations for digging in living and extinct ctenomyid and octodontid rodents - Lessa, Enrique P. (2008)
To examine the evolution of burrowing specializations in the sister families Octodontidae and Ctenomyidae (Rodentia: Caviomorpha), we produced a synthetic phylogeny (supertree), combining both molecular and morphological phylogenies, and including both fossil and extant genera. We mapped morphological specializations of the digging apparatus onto our phylogenetic hypothesis and attempted to match morphological diversity with information on the ecology and behaviour of octodontoid taxa. Burrowing for sheltering and rearing is the rule among octodontids and ctenomyids, and adaptations for digging have been known from the Early Pliocene onward. However, only a few taxa have evolved fully subterranean habits. Scratch-digging is widespread among both semifossorial and fully subterranean lineages, and morphological changes associated with scratch-digging are not restricted to subterranean lineages. By contrast, various adaptations for chisel-tooth digging are restricted to some subterranean lineages and are combined differently in the octodontid Spalacopus, the fossil ctenomyid Eucelophorus, and some living Ctenomys. Some octodontid taxa are able to dig complex burrows in spite of having no substantial changes in musculoskeletal attributes. Hence, we suggest that, during the early evolution of those branches giving rise to fully subterranean ctenomyids and octodontids, a change in behaviour probably preceded the origin of structural adaptations.